Theological Libraries and Library Associations in Europe (Brill, 2024)
During the past 50 years, theological libraries have confronted secularisation and religious pluralism, along with revolutionary technological developments that brought not only significant challenges but also unexpected opportunities to adopt new instruments for the transfer of knowledge through the automation and computerisation of libraries. This book shows how European theological libraries tackled these challenges; how they survived by redefining their task, by participating in the renewal of scholarly librarianship, and by networking internationally. Since 1972, BETH, the Association of European Theological Libraries, has stimulated this process by enabling contacts among a growing number of national library associations all over Europe.